Potensi Pembinaan Ekonomi Masyarakat melalui Berbagai Kegiatan di Masjid Tahtasyajaroh Kampung Pasir Angin Kiambon Desa Warga Jaya Kecamatan Cigudeg – Bogor - Hilman, Agus; Qurni, Uwaesul (ALIF: Sharia Economics Journal, 2024)
Strategically nom, mosque can function as educational institutions to Foster the economic potential of people from various backgrounds. Education and community development that can be Carried out include coaching from religious, scientific, social, economic, health, artistic and cultural aspects.  Seeing the function of mosques which is very important in fostering people to become intelligent and prosperous human beings, of course we as academics do not want to be left behind to take and active role in realizing this.  This time, through real work lectures (KKN) in the village of Pasir Angin kiambon village Wargajaya Cigudeg District Bogor Regency, it is the right momentum to increase the prosperity of the mosque students together with the community, in this case the congregation of the Tahtassyajaroh mosque, Carried out many activities. The activities include recitation of the Qur'an, five daily prayers in congregation, evening recitation on Monday and Priday, the Maghrib Qur’an movement, clean operations, gardening around the mosque, business discussion in the style of islamic economic and so on. The most important task now is how to maintain this moment of togetherness so that it continues to be sustainable and the impact is felt in the community, so that in the end it Will create a society that has intellectual, spiritual, religious, qualification which are the moral basis of the Indonesian people. This spirit Will continue to be Carried out, even when the actual work lecture (KKN) activities have been completed.